Environmental Impact Assessment Initiated to Mitigate Pollutions from Industries - Shadika Haque Monia (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2020)
Industrial pollution is a Buzzword of the present world. At the same time, there needs industrial development along with the mitigation of pollution, but in practice, industries are increasing with polluters although protection of pollution is lagging. The conservation of natural wealth is growing through various processes without thinking about the future. As an overpopulated country, a large number of industries have been contributing to enrich the economy of Bangladesh. In addition to there is no specific legal mechanism in the country to control industrial pollution which causes danger for the environment. The paper endeavors to find out the present legal instruments regarding environmental pollution caused by industries in Bangladesh, whether these are sufficient to prevent such pollution or not. Therefore, there is no specific legislation under IEL to mitigate industrial pollutions The research will contribute to the courtier's policymaking in the field of environmental protection, very few research has done in this area. As there is no specific legislation dealing with industrial pollutions, the Article tries to facilitate the need for specific legislation or mechanism on this matter by mentioning critics of existing legislations and found that, in absence of specific legislation the country is facing environmental threats every day. The data is analyzed with qualitative methods, both primary and secondary data is analyzed for the same. The research is done with doctrinal based analytical research.